O10-2 Maternal occupational exposure assessment to extremely low frequency electromagnetic fields (ELF-EMF) and pregnancy outcomes in the elfe cohort. (1st September 2016) - Migault, Lucile; Schwall, Xavier; Piel, Clément; Leffondre, Karen; Lacourt, Aude; Cardis, Elisabeth; Bowman, Joseph D; Baldi, Isabelle; Seze, René de; Bouvier, Ghislaine
Abstract : Background: Despite the widespread and increasing use of electricity in working environments, occupational exposure to ELF-EMF during pregnancy has been rarely documented and was often assessed using the mothers' self-report. Our first aim was to assess maternal occupational exposure to ELF-EMF during pregnancy in the birth cohort study Elfe. Secondly, we studied the link between this exposure and child's gestational age or birth-weight. Methods: The Elfe study was initiated in 2011 in France and enrolled more than 18, 000 infants born between 33 and 42 weeks' gestation. Mother's job title was collected by a face-to-face interview and coded using the International Standard Classification of Occupation 1968 (ISCO68). The Bowman population-based job exposure matrix (JEM) was used to assess arithmetic-mean-workday ELF-EMF exposure level associated to the occupation held by each mother during pregnancy, expressed in µT/day. This JEM used the Standard Occupational Classification system 1980 (SOC80). ISCO68 codes were translated to their SOC80 equivalent. Exposure levels were categorised according to quartiles and 90th percentile. Multiple linear regression models were used to estimate adjusted differences in mean birth-weight and mean gestational age between exposure groups. Results: A total of 13, 340 mothers worked during their pregnancy. Job was coded into SOC80 for 12, 671 mothers and mean-workday level was defined for 12, 549. Adjusted models did not show differences between any of the exposure groups and the reference category for both birth-weight and gestational age among children born at 33 weeks' gestation or more. Conclusion: Our study, in a large birth cohort, is the first to assess maternal occupational exposure during pregnancy using a JEM based on industrial hygiene measurements. Our next aim will be to use the INTEROCC ELF-JEM (http://www.crealradiation.com ), an updated version of the Bowman ELF-JEM. We will also assess environmental exposure to ELF-EMF during pregnancy and its possible association with birth outcomes.